ASSESSMENT OF HAZARD PERCEPTION FROM PACKAGES SHAPES - Ayanoğlu, Hande; Duarte, Emília; Teles, Júlia (Ergodesign & HCI, 2015)
TITLE: Assessment of hazard perception from packages shapes: a comparison of visualization methos ABSTRACT User safety could be increased by package designs that promote an adequate hazard perception. Different methodologies are available to conduct studies about the influence of package variables on users’ perceptions. This paper presents a comparative study of two visualization methods (2D vs 3D) to assess hazard perception from household packages’ shape. Household Packages, Hazard Perception, Virtual Reality